Domestic Violence in the Canadian Workplace: Are Coworkers Aware? - Jennifer C.D. MacGregor; C. Nadine Wathen; Barbara J. MacQuarrie (Elsevier, 2016)
Background: Domestic violence (DV) is associated with serious consequences for victims, children, and families, and even national economies. An emerging literature demonstrates that DV also has a negative impact on workers and workplaces. Less is known about the extent to which people are aware of coworkers' experiences of DV. Methods: Using data from a pan-Canadian sample of 8,429 men and women, we examine: (1) awareness of coworker DV victimization and perpetration; (2) the warning signs of DV victimization and perpetration recognized by workers; (3) whether DV victims are more likely than nonvictims to recognize DV and its warning signs in the workplace; and (4) the impacts of DV that workers perceive on victims'/perpetrators' ability to work. Results: Nearly 40% of participants believed they had recognized a DV victim and/or perpetrator in the workplace and many reported recognizing more than one warning sign. DV victims were significantly more likely to report recognizing victims and perpetrators in the workplace, and recognized more DV warning signs. Among participants who believed they knew a coworker who had experienced DV, 49.5% thought the DV had affected their coworker's ability to work. For those who knew a coworker perpetrating DV, 37.9% thought their coworker's ability to work was affected by the abusive behavior. Conclusion: Our findings have implications for a coordinated workplace response to DV. Further research is urgently needed to examine how best to address DV in the workplace and improve outcomes for victims, perpetrators, and their coworkers.